GIS Analysis of Flood Vulnerable Areas In Benin- Owena River Basin, Nigeria - Adebayo Oluwasegun Hezekiah (Faculty of Geography, Universitas Gadjah Mada, 2017)
The frequency and intensity of flood disasters have become serious issues in the national development process of Nigeria as flood disasters have caused serious environmental damages, loss of human lives and other heavy economic losses; putting the issue of disaster reduction and risk management higher on the policy agenda of affected governments, multilateral agencies and NGOs. The starting point of concrete flood disaster mitigation efforts is to identify the areas with higher risk levels and fashion out appropriate preventive and response mechanisms. This research paper explored the potentials of Geographic Information System (GIS) in data capture, processing and analysis in identifying flood-prone areas for the purpose of planning for disaster mitigation and preparedness, using Benin-Owena river basin of Nigeria as a unit of analysis. The data used in this study were obtained from FORMECU and were entered and use to develop a flood risk information system. Analysis and capability of the developed system was illustrated and shown graphically. The research showed that over one thousand settlements harbouring over ten million people located in the study area are at grave risk of flooding. Key words: Flood, Risk, Vulnerability, Geographical Information System (GIS), River -Basin